2008
DOI: 10.1590/s1413-78522008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Artroplastia total do quadril de Spotorno®

Abstract: Uma coorte de 48 pacientes (54 quadris) submetidos a artroplastia total primária de quadril não-cimentada com prótese de Spotorno®. O objetivo do estudo foi avaliar o desfecho clínico-radiológico da prótese de Spotorno®,em um período de 20 anos (1985 a 2005), com seguimento médio de 17,5 anos (8-20anos). Na avaliação clínica e funcional foram obtidos 92,7% de bons resultados. Encontrou-se osteopenia em 24 acetábulos (44,4%) e 30 fêmures (55,6%). O desgaste do polietileno esteve presente em 43 acetábulos (79,6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…The clinical assessment showing that 80% of the results were good and very good was similar to what was found in a study using the Spotorno ® prosthesis, a foreign model that formed the basis for the development of the prosthesis under examination here 13 , 14 , 18 , 19 . In the statistical analysis on the clinical outcome over the follow-up period, it was observed that there was a gradual decrease in functional grade as the length of follow-up increased, with P = 0.008.…”
Section: Discussionsupporting
confidence: 80%
“…The clinical assessment showing that 80% of the results were good and very good was similar to what was found in a study using the Spotorno ® prosthesis, a foreign model that formed the basis for the development of the prosthesis under examination here 13 , 14 , 18 , 19 . In the statistical analysis on the clinical outcome over the follow-up period, it was observed that there was a gradual decrease in functional grade as the length of follow-up increased, with P = 0.008.…”
Section: Discussionsupporting
confidence: 80%
“…Every year about 800,000 THA are performed worldwide, and it is estimated that this number will increase in the future second (Kilis, 2003) is widely used surgical procedure for the treatment of disorders of the hip joint, whether degenerative, inflammatory or traumatic concluded (Macedo, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico and other Latin American countries, it was a popular implant throughout the 90s and 2000s. 2,3 Even though the stem has reported excellent long-term results in multiple published series, there is a high incidence of revision because of the failure of the cup. The cup has been reported to fail because of the breakage of the metal backing or severe polyethylene wear.…”
mentioning
confidence: 99%
“…The cementless System (CLS) uncemented total hip replacement system was designed by Lorenz Spotorno in 19841 and extensively used in Europe over the past 2 decades. In Mexico and other Latin American countries, it was a popular implant throughout the 90s and 2000s 2,3…”
mentioning
confidence: 99%